A Third Form of Righteousness: The Theme and Contribution of Matthew 6.19–7.12 in the Sermon on the Mount - Wilson, Walter T. (New Testament studies, 2007)
Although there is agreement that the body of the Sermon on the Mount (SM) contains three parts, there is little consensus regarding the nature of the third part. This passage is compared with different examples of wisdom instruction, each of which offers a unified composition on the moral problem of ‘goods’, broadly conceived as that which confers good standing or status, not only in economic terms but in social and spiritual terms as well. This provides a perspective from which to examine the overall structure of the sermon in the light of certain practices evident in ancient texts for organizing moral discourse.